The overtourism debate : NIMBY, nuisance, commodification - Oskam, Jeroen (Emerald Publishing Limited, 2020)
This book gives an overview of the positions in the rapidly evolving debate over the sociocultural footprint of tourism on its destinations. Overtourism, its impact and subsequent mitigating measures taken, have started to dominate political discussions in European cities such as Amsterdam, Barcelona, Seville and Berlin.
Includes index.
Keywords: Overtourism -- Europe.; Tourism -- Management.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books